PENGARUH SUPLEMENTASI MINYAK MAGGOT TERHADAP PERFORMA AYAM PETELUR: THE EFFECT OF MAGGOT OIL SUPPLEMENTATION ON LAYING HEN PERFORMANCE - Anwar, Baharudin; Purwati, Catur Suci (Universitas Boyolali, 2025)
This study was conducted to examine the effect of maggot oil (Hermetia illucens) supplementation in rations on the performance of laying hens, especially on the variables of feed consumption, egg weight, egg production, and feed conversion ratio (FCR). Maggot oil is an alternative fat source that is rich in essential fatty acids and has the potential to improve metabolic performance and chicken productivity. This study used an experimental design with several levels of maggot oil supplementation and one control group without treatment. The results of the analysis showed that maggot oil supplementation did not have a significant effect on egg weight and FCR values, so it did not change the efficiency of feed utilization or the weight of eggs produced. However, maggot oil supplementation had a significant effect on increasing daily feed consumption and egg production. Chickens that received maggot oil showed an increase in appetite, which was likely due to increased feed palatability due to the fat content in maggot oil. This increase in consumption then had an impact on high hen day production (HDP), indicating that maggot oil was able to encourage higher egg production. Based on these findings, it can be concluded that maggot oil has the potential as an alternative feed additive that can improve the performance of laying hens in terms of egg productivity and feed consumption, without reducing the efficiency of feed conversion or the quality of the egg weight produced.